2009
DOI: 10.1111/j.1539-6924.2008.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Real‐World Personal Conversations Using a Hands‐Free Embedded Wireless Device While Driving: Effect on Airbag‐Deployment Crash Rates

Abstract: A wireless device embedded in the vehicle allowed the user to engage in a personal hands-free conversation (HFC), and automatically placed an emergency notification call to an OnStar call center if the vehicle was involved in a crash in which its airbag deployed. A database stored the exact counts, start timestamps, and billed durations of all HFC and airbag notification calls. In 30 months of naturalistic driving, there were 91 million HFC calls from an average of 323,994 drivers per month who made calls. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 43 publications
(124 reference statements)
4
37
2
2
Order By: Relevance
“…Differences between the VTTI 100-Car OR estimate for Talk 1 and those from independent real-world studies 2,3 led to the question of whether methodological issues could underlie the differences. A Standard Method of epidemiological analysis using the 100-Car databases was compared to published results from the VTTI Method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences between the VTTI 100-Car OR estimate for Talk 1 and those from independent real-world studies 2,3 led to the question of whether methodological issues could underlie the differences. A Standard Method of epidemiological analysis using the 100-Car databases was compared to published results from the VTTI Method.…”
Section: Discussionmentioning
confidence: 99%
“…1,11 The Standard Method was free of this bias and error, and estimated OR and P e % effect sizes for Talk which were consistent with those in independent studies. 2,3,13,14 Root Cause of Positive OR Bias. The VTTI Method 1,11 caused high OR estimates because it counted only at-fault unexposed cases (which enter the OR denominator), but counted all cases, regardless of fault, for the exposed cases (which enter the OR numerator).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young and Schreiner (2009) hypothesize that the low crash risk in their real-world study "can be explained if drivers making personal wireless calls using the OnStar embedded hands-free calling device are taking responsibility to: (1) make prudent and safe choices about engaging in calls during adverse road, environmental, or traffic conditions, (2) reduce or postpone elective driving maneuvers or secondary tasks that might increase crash risk when in a call, and (3) adapt conversations while in a call to accommodate road and traffic conditions." Drivers might also be compensating for the predicted small RT increases from hands-free conversations using this device by simply taking extra care to keep their eyes on the road, hands-on-the-wheel, and mindon-the-drive.…”
Section: Real-world Implicationsmentioning
confidence: 99%
“…A recent real-world epidemiological study (Young and Schreiner, 2009) compared personal conversation crash rates to no-conversation crash rates using a hands-free wireless device "embedded" or built into the vehicle. This study found no increase in airbag-deployment crash rates for personal conversations using the device, compared to driving without conversing on the device, consistent with the low crash risk found by Young (2001) for calls to an OnStar advisor.…”
Section: Real-world Implicationsmentioning
confidence: 99%